Статистичний аналіз ДКП коефіцієнтів JPEG зображень - Куріний, А. А. (ХНУРЕ, 2020)
Digital technologies allow people to receive and process enormous general information and securely store it. Presently, one of the most important tasks is the creation of compression methods, the use of which allows improving the characteristics of the system of transmission, processing and data registration. The purpose of this work is to substantiate the expediency of choosing the Laplace distribution for the statistical description of DCT coefficients from a statistical point of view. The main idea of the work is to use a double stochastic model, according to which not only DCT coefficients but also the variance of these coefficients will be considered random